Experiences of school health nurses regarding the provision of the school health service delivery in the Tshwane district - Selebetswe T. Dibakwane (African Journal of Primary Health Care & Family Medicine, 2018)
Background: Irrespective of the provision of an integrated school health policy, the school health nurses continue to experience multiple challenges regarding the provisioning of school health service delivery.